Managing the competitiveness of hockey players of the sports reserve - Rotenberg R.B. , (Theory and Practice of Physical Culture, 2025)
This study examines the issues of effective organization of long-term training of hockey players of the sports reserve. The practical aspect of the study is related to the solution of the problem of maintaining the competitiveness of athletes in the conditions of their transition to professional hockey teams, close in requirements to the sport of the highest achievements. The methodological basis of the study is modern ideas about the laws of the process of formation of sports mastery of Yu.V. Verkhoshansky, as well as the «concept of the system-forming factor» of the theory of functional systems of P.K. Anokhin.